Environmental assessment of catering service operations in Jitra, Malaysia - Nasrudin, Nazatul Syifa; Shafie, Farah Ayuni; Zulkeflee, Zufarzaana; Zaki, Muhammad Afiq (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: The entire human food supply system can be susceptible to food loss. Catering services is one of the major creators of substantial amounts of food waste. This causes a detrimental impact on socio economic and environmental sustainability. This study was aimed to examine the food waste and carbon footprint from catering operations which have expanded into an industry. These operations particularly expanded due to its social and economic significance in the growing town of Jitra, Kedah. Methods: Five catering services were selected to represent the catering operations. Food waste was categorized based on waste from preparation loss, serving loss and plate loss of the customer. The loss categories were differentiated by three colour-coded containers and were weighed in-situ. This was followed by determination of carbon footprints from the electricity and water consumption during the catering operations. Material Flow Analysis was used to visualize the material flow from the catering services’ operations. Results: Customer plate waste contributed to the majority of the food waste, accounting for 54.47% of the waste, while preparation loss produced 45.53% of the food waste. The catering services produced roughly 11.87 kgCO2 e of carbon footprint from the average electricity consumption, and had an average power usage of 108.58 kWh. Meanwhile, for the total average of water consumption, the catering services used up to 5.71 m3 of water on a daily average, which may produce 22.71 kgCO2 e of carbon footprint. Conclusion: : This study was not designed for a detailed examination of food waste generated by catering services, but rather on how variables that affect food waste generation and carbon footprint could be included. Therefore, this study assisted the management of catering services in identifying areas for improvement including resource management to reduce the generation of food wastes.